Dryad Dataset_PLOS ONE_Great Slave Lake Fish Metal(loid)s - Chételat, John; Cott, Peter A. (Dryad Digital Repository, 2019)
This file contains measurements of metal(loid) concentrations and ancillary data for fishes of Great Slave Lake, Northwest Territories, Canada. The worksheets contains: (1) Locations of fishes captured during the study; (2) Size, age, metal(loid) concentrations, and carbon and nitrogen stable isotopes of fishes captured for the study; (3) Size, age, and metal(loid) concentrations of fishes reported in 2 grey literature technical reports on the study area; (4) Size and metal(loid) concentrations of fishes examined in a previous publication (Cott et al. 2016.Journal of Great Lakes Research 42(2):223-32).